Peran Manajemen Pendidik dalam Meningkatkan Mutu Kualitas Sekolah - An Nisaa Zukhrufatul; Dahlia Fitri Ichsanti; Farid Setiawan (Arus Jurnal Pendidikan, 2023)
The success that schools have can be seen how the division of tasks in designing, mastering and even managing organizations or groups to improve quality. To find out how to set up a management system so that schools can improve their quality. This study uses data collection methods or literature learning. In improving the quality of schools, several roles of educators are needed, namely (1) the role of the teacher in building, seeking and finding focused learning; (2) The role of the teacher during teaching and learning activities needs to apply creativity and initiative. because conventional education is very inclined to show the mechanical skills that a person has in completing the work he faces.; (3) The role of the teacher during teaching and learning activities needs to apply interactions between fellow educators and other students and work together in a team.